PERSPEKTIF BUDAYA MARITIM INDONESIA (Sebuah Refleksi Sejarah Antropologi Oseania) - Gregor Neonbasu SVD (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2022)
This article discusses two basic points: firstly, Indonesian Maritime Trade and secondly, Oceanic Anthropological History. The first point will be studied in classical comprehension spectrum related to maritime wealth and the image of Indonesians’ competency image in the past all at once. The second point focuses on anthropological speculation concerning unity and wholeness of various lands in Oceania. Some official sources become the reference in this article, including our study that has been conducted for almost 6 years, since 2015 – today (2020) and is still continued. Specific source becoming special reference in this article is the application of historical reflection by Bernard H.M. Vlekke entitled Nusantara: A History of Indonesia (1961), a work revealing the historical evidence of Archipelagic (Indonesian) civilization in the past.